Counselling sessions increased duration of exclusive breastfeeding: a randomized clinical trial with adolescent mothers and grandmothers - Dias de Oliveira, Luciana (BioMed Central, 2014)
BACKGROUND: Considering that adolescent mothers may be more vulnerable to discontinuing exclusive breastfeeding (EBF) before 6 months and that their mothers may exert a negative influence on this practice, this study was conducted with the objective of evaluating the efficacy of breastfeeding counselling for adolescent mothers and their mothers in increasing EBF duration. METHODS: A clinical trial was performed in 323 adolescent mothers with newborns and their mothers randomized in four groups: (1) not living with mother, without intervention; (2) not living with mother, with intervention; (3) living with mother, without intervention, (4) living with mother, with intervention. The intervention consisted of five counselling sessions directed to mother and grandmother, in the maternity hospital and on follow-up. Information about feeding practices during the newborn’s first six months of life was collected monthly by telephone. Intervention’s efficacy was measured through Cox regression and comparison of exclusive breastfeeding medians and survival curves for the different groups. RESULTS: The intervention increased the duration of EBF by67 days for the group which included grandmothers (HR = 0.64; CI 95% = 0.46-0.90) and 46 days for the group which did not include grandmothers (HR = 0.52; CI 95% = 0.36-0.76). CONCLUSIONS: Counselling sessions in the first four months of children’s lives proved to be effective in increasing EBF duration among adolescent mothers. TRIAL REGISTRATION: ClinicalTrials.gov NCT00910377.